2017
DOI: 10.1007/s11250-017-1394-5
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes and practices towards cystic echinococcosis in livestock among selected pastoral and agro-pastoral communities in Uganda

Abstract: A cross-sectional study was done from March 2013 to May 2014 to assess knowledge, attitudes, and practices towards cystic echinococcosis (CE) or hydatidosis among selected pastoral and agro-pastoral communities in Uganda. A structured questionnaire was administered to 381 respondents. Multivariate logistic regression analysis was done to find the relationship between knowledge about CE and factors such as age, sex, and level of education across all regions. The odds ratio and confidence interval were used to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 27 publications
3
17
0
Order By: Relevance
“…Approximately half of respondents dewormed their livestock; however, more than a quarter of them did not have a regular deworming interval for their livestock. The findings on the number of dog keepers who dewormed their dogs is consistent with a study done in Uganda [16], but was in contrast to studies done in Ethiopia where dog keepers were 71% of the study participants and none of them dewormed their dogs [19] and in Pakistan where dog keepers were 64% and 68% of them dewormed their dogs [7]. The dog owners did not know the risk contained in improper disposal or inappropriate handling of dog faeces in terms of transmission of CH.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Approximately half of respondents dewormed their livestock; however, more than a quarter of them did not have a regular deworming interval for their livestock. The findings on the number of dog keepers who dewormed their dogs is consistent with a study done in Uganda [16], but was in contrast to studies done in Ethiopia where dog keepers were 71% of the study participants and none of them dewormed their dogs [19] and in Pakistan where dog keepers were 64% and 68% of them dewormed their dogs [7]. The dog owners did not know the risk contained in improper disposal or inappropriate handling of dog faeces in terms of transmission of CH.…”
Section: Discussionsupporting
confidence: 90%
“…The findings of the KAP survey showed that the beef value chain in the study area was dominated by men, who have culturally been cattle traders and they tend to dominate livelihood activities that generate financial income as was seen in studies done in Uganda [16] and Pakistan [7]. Most of the participants, especially farmers, did not have much knowledge about hydatidosis.…”
Section: Discussionmentioning
confidence: 91%
“…In addition, they engaged in skinning and therefore handling raw hides because of the high market value of camel leather and hair [32]. Since our study also found that lack of formal education was an important risk factor associated with increased risk of brucellosis infection, we envision that promoting formal education among the pastoralists would result in improved economic opportunities and reduction in risky practices as has been observed in other studies [33,34].…”
Section: Discussionmentioning
confidence: 51%
“…It was shown that when age of the people is increased the awareness about CE increased too. 16 , 34 The participants generally knew more about CE as their age increased ( p <0.05). In a recent study by Othieno et al female gender, age beyond 40 years, and open spring water sources were the main risk factors for CE in humans.…”
Section: Discussionmentioning
confidence: 96%
“…This was a descriptive study to assess the awareness of risk factors of CE among different occupational groups. 16 Questionnaire forms were prepared in compliance with the individuals’ diversity. Participants were classified into 3 groups, and a different survey was created for each group.…”
Section: Methodsmentioning
confidence: 99%